Assessing the First Shocks of the Covid-19 Pandemic on the Idiosyncratic Risk in the Brazilian and the Others Emerging Markets - Assis de Salles, Andre (Technium Business and Management, 2023)
The Covid-19 Pandemic has affected social and economic relations in the world economy, the national economies, and the financial markets. The production investment and financing in economies occur through these markets, particularly in the capital market. The idiosyncratic risk, one of the two total risk components, is associated with a specific productive project, an economic sector, a specific national economy or a capital market. This work aims to estimate the idiosyncratic risk of the Brazilian economy through heteroscedastic conditional models, to verify the initial impact of the Covid-19 Pandemic on the risk associated with productive projects developed in the Brazilian economy and the emerging economies. Daily data in US$, spanning from June 30, 2017, to July 1, 2020, were used.